Video Edukasi Animasi 2d Tentang Pemilu 2024 Untuk Perum Lkbn Antara Biro Kepulauan Riau - Chantiequ, Angiela; Kanistren, Aragani Timur (JOURNAL OF APPLIED MULTIMEDIA AND NETWORKING, 2025)
First-time voters play a significant role in the 2024 elections in Batam City, necessitating engaging and accessible information media to enhance audience engagement. Therefore, a 2D animated educational video was developed as a platform for socialization and disseminated through digital platforms. The design method used was the Multimedia Development Life Cycle (MDLC), which consists of six main stages: Concept, Design, Material Collection, Assembly, Testing, and Distribution. Testing was conducted using the EPIC Model, which encompasses four aspects: Empathy, Persuasion, Impact, and Communication. The 2D animated video proved effective in educating first-time voters in Batam about the 2024 elections, combining visual elements and narrative information to reinforce the message.